Integrated Piezo-Triboelectric Nanogenerators-Based Self-Powered Flexible Temperature and Pressure Sensor - Min, Guanbo; Khandelwal, Gaurav; Dahiya, Abhishek Singh; Mulvihill, Daniel M.; Dahiya, Ravinder (IEEE journal on flexible electronics, 2023)
Efficient harvesting of ubiquitous ambient mechanical energy using various types of nanogenerators (NGs) has attracted considerable interest in recent years. Herein, we present a textile triboelectric NG (T-TENG) using polytetrafluoroethylene (PTFE) and nylon-based counter-surfaces in fabric form (both fixed to conductive fabric electrodes). T-TENG performance is enhanced by exposing a PTFE film with argon (Ar) plasma. The output voltage of the plasma-treated devices increased by a factor of ~10, and their short-circuit current density increased by a factor of ~9 (compared to pristine nonplasma-treated devices). Additionally, we demonstrate that the fabricated T-TENG can be used as a self-powered temperature sensor, tested in the 25 °C-90 °C range. The T-TENG output voltage decreased linearly with increasing temperature exhibiting a sensitivity of \boldsymbol {\sim }1 %/°C. Furthermore, we integrated a flexible piezoelectric NG (PENG) on top of the T-TENG to detect the contact forces. The PENG output is also used to compensate for the pressure-dependent output of TENG underneath and allows distinct temperature and pressure measurements. The excellent results observed here show the potential of T-TENGs for use as self-powered sensors in applications such as health monitoring, wearables, and interactive systems.